Educação popular, educação do campo e multiterritorialidade do Movimento dos Trabalhadores Rurais Sem Terra: estudo do assentamento unidos de Santa Bárbara - Sítios Novos - Caucaia - Ceará - Castro Júnior, José Lima (2005)
The envelopment with theme and confirmation of inefficient theoretical methodological studies of professionals, researchers, settled people and militants of Agrarian Reform that they discriminated education and territories, linking that false dichotomy - history and geography, theory and practical, in loco or global - in the context of resistances, fights and alternative for globalization, it is the start point to study the relation between Popular Education, Country Education and MST Multiterritorializing. Having how unit of study the Santa Bárbara Assettlement, in Ceará, the methodological way of the work, of qualitative importance and ethnographic, it gives voice to subjects and reconstitute historically the production processo of knowledges. I debates the Country Education like blanks for the Agrarian Reform and the territories those are action place and power in the daily transformation of Landless, it gives with popular multiterritorializing. It presents theorical limits from daily, detaching the popular education, country education and MST Multiterritorializing. It gives course to work showing how occur the construction of knowledges, from spontaneity to rationality, with the actors deeping and “amplifying” territory, practicing roles to construct territories, and identities and, the MST, as subject of its Multiterritorializing. It shows tha other hand of spontaneous knowledges, that is the unterritorializing and the territorializing, with a cartographic, a Multiterritorializing drawing, the strategies realized by settled people satisfying requirements, the issue point or the montage of issue, as learning by participation. The initiation of the rational knowledge production shows with a educação presence, that live together between subordinated and edify the popular power, in the same time that are elevated learning that amplify the MST presence in Ceará, in Brazil and in the World. It concludes making a reflexion, Popular Multiterritorializing: how, where and why? Returning to investigative problem raise practical implications, dismystifying the dichotomy theory and practical, as a contribution for the academy. Following with lessons given by the MST, emphasizing implications for the public politicians and, finally, raise points in relation to research, underlining theorical and methodological limitations, attach the difficulties of the formative process of the researcher, as well, still, disposable aspects and ideas for the future.